Recover energy from domestic wastewater using anaerobic membrane bioreactor: Operating parameters optimization and energy balance analysis. (1st March 2016) - Mei, Xiaojie; Wang, Zhiwei; Miao, Yan; Wu, Zhichao
Abstract: Anaerobic membrane bioreactor (AnMBR) is a promising process to recover energy and water resource from domestic wastewater; however, its energy-efficiency needs substantial improvement for real applications. In this study, based on the methanogenic activity batch tests and critical flux determination, an optimization protocol for AnMBRs is reported and a flux-centered energy balance analysis is conducted. The results demonstrate that organic loading rate by sludge (OLRsludge ) should be controlled within 0.43–0.90 kgCOD/(kgVSS·d), and the corresponding sludge retention time (SRT) should be in the range of 50 d to infinity. Energy balance analysis shows that the AnMBR systems at the temperature of 35 °C and 25 °C could achieve net energy recovery. For realizing energy-neutral operation, the corresponding fluxes should range from 8.3 to 9.5 L/(m 2 ·h) at 35 °C and 6.0 to 6.7 L/(m 2 ·h) at 25 °C, respectively. In the process design and operation, a relatively short hydraulic retention time (HRT) and an SRT close to 50 d should be considered in order to achieve an energy-efficient AnMBR performance. Highlights: An optimization protocol for AnMBRs was developed to maximize energy recovery. OLRsludge and SRT should be controlled at 0.43–0.90 kgCOD/(kgVSS·d) and above 50 d, respectively. Relatively short HRT and SRT should be considered in the process design and operation. The AnMBR systems at 35 °C and 25 °C could achieve net energy recovery.